ANALYSIS OF FACTORS AFFECTING BOUNDING ATTACHMENT BETWEEN MOTHER AND BABY IN THE POSTPARTUM IN CLINIC BATUA RAYA MAKASSAR - kartika kartika (Stikes Graha Edukasi Makassar, 2019)
Introduction: Bounding Attachment implementation in the clinic Batua Raya Makassar carried out from the stage 3 to postnatal care, which held the contact between mother and baby are in a bond of love.This study aimed to analyze the factors that affect Bounding attachment between mother and baby during childbirth at health centers in Batua Raya Makassar.Method: This research method using Analytic survey with cross sectional approach. With a total population of 78 mothers who gave birth to normal and Samper 65 puerperal women, with purposive sampling. Results: The results show that knowledge get ? = 0.031, parity ? = 0, 005, and the role of midwife ? = 0.000. Where ? <? = 0.05. The result showed that there is a relationship between knowledge, parity, and the midwife's role on the implementation of Bounding attachment between mother and baby during childbirth at health centers in Batua Raya Makassar 2016.